2021
DOI: 10.1371/journal.pone.0260456
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of right ventricular native T1 mapping in pulmonary arterial hypertension

Abstract: Background Right ventricular function is an important prognostic marker for pulmonary arterial hypertension. Native T1 mapping using cardiovascular magnetic resonance imaging can characterize the myocardium, but accumulating evidence indicates that T1 values of the septum or ventricular insertion points do not have predictive potential in pulmonary arterial hypertension. We aimed to elucidate whether native T1 values of the right ventricular free wall (RVT1) can predict poor outcomes in patients with pulmonary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Native T1 and ECV in our study correlated well with RV hemodynamics and function, particularly at RVIP and septal regions. These findings are in good agreement with previous studies on the PH population, which found a moderate to strong correlation between native T1 at the insertion point and septal region with mPAP, PVR, and RV ejection fraction ( 43 46 ). Global RV and septal ECV were also shown to correlate to mPAP and RV function ( 21 , 47 ).…”
Section: Discussionsupporting
confidence: 93%
“…Native T1 and ECV in our study correlated well with RV hemodynamics and function, particularly at RVIP and septal regions. These findings are in good agreement with previous studies on the PH population, which found a moderate to strong correlation between native T1 at the insertion point and septal region with mPAP, PVR, and RV ejection fraction ( 43 46 ). Global RV and septal ECV were also shown to correlate to mPAP and RV function ( 21 , 47 ).…”
Section: Discussionsupporting
confidence: 93%
“…Cardiac T1 mapping provides valuable quantitative information for the diagnosis of a variety of heart diseases (Schelbert and Messroghli 2016, Haaf et al 2017, Al-Wakeel-Marquard et al 2021. While in clinical routine diagnostics are more focused on the left ventricle, quantitative imaging of the right ventricular wall (Asano et al 2021) or the atrial wall (Beinart et al 2013) is also of high diagnostic value. Isotropic high-resolution whole-heart coverage would strongly improve diagnostic information about fibrosis in atrial walls in arrhythmic patients (Beinart et al 2013) and improve diagnostic capability in patients with pulmonary arterial hypertension (Asano et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While in clinical routine diagnostics are more focused on the left ventricle, quantitative imaging of the right ventricular wall (Asano et al 2021) or the atrial wall (Beinart et al 2013) is also of high diagnostic value. Isotropic high-resolution whole-heart coverage would strongly improve diagnostic information about fibrosis in atrial walls in arrhythmic patients (Beinart et al 2013) and improve diagnostic capability in patients with pulmonary arterial hypertension (Asano et al 2021). As these structures are usually very thin (Whitaker et al 2016) (between 1 and 4 mm) and complexly curved, high spatial resolution is needed.…”
Section: Introductionmentioning
confidence: 99%
“…This has meanwhile favored, that parametric imaging is subject of multiple studies in patients with different etiologies of pulmonary hypertension (PH). So far, pathological elevations of cardiac native T1 time and extracellular volume (ECV) compared to healthy volunteers, promising correlations to functional and hemodynamic parameters and influences on patient outcome and survival have already been demonstrated [ 2 , 3 , 4 , 5 , 6 , 7 , 8 ]. Even more, parametric imaging seems to be suitable to investigate therapy effects—for example, of balloon pulmonary angioplasty (BPA)—on cardiac function and pulmonary hemodynamic in chronic thromboembolic pulmonary hypertension (CTEPH) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%